Tenofovir and Doravirine Are Potential Reverse-Transcriptase Analogs in Combination with the New Reverse-Transcriptase Translocation Inhibitor (Islatravir) Among Treatment-Experienced Patients in Cameroon: Designing Future Treatment Strategies for Low- and Middle-Income Countries - Alex Durand Nka; Yagai Bouba; Wilfried Rooker Tsapi Lontsi; Davy-Hyacinte Gouissi Anguechia; Georges Teto; Aude christelle Ka’e; Ezechiel Ngoufack Jagni Semengue; Collins Ambe Chenwi; Désiré Takou; Lum Forgwei; Tatiana Anim-Keng Tekoh; Aurelie Minelle Kengni Ngueko; et al. (Viruses)
Islatravir (ISL) is a novel antiretroviral that inhibits HIV-1 reverse transcriptase translocation. The M184V mutation, known to reduce ISL’s viral susceptibility in vitro, could arise from prolonged exposure to nucleoside reverse transcriptase inhibitors (NRTI) (3TC). This study evaluated the predictive efficacy of ISL and identified potentially active antiretrovirals in combination among treatment-experienced patients in Cameroon, where NRTIs (3TC) have been the backbone of ART for decades now. Although ISL is a long-acting antiretroviral, it will provide other therapeutic options in combination with other reverse transcriptase inhibitors that remain effective. We analyzed 1170 HIV-1 sequences from patients failing first-, second-, and third-line ART using the CIRCB Antiviral Resistance Evaluation (CIRCB-CARE) database. Drug resistance mutations (DRMs) were interpreted using Stanford HIVdb.v9, and covariation patterns between M184V and major NRTI/NNRTI DRMs were assessed. The study population, with a median age of 40 years, showed a high prevalence of resistance to NRTIs (77.4%) and NNRTIs (49.2%). The most frequent NRTI DRMs were M184V/I (83.3%), M41L (25.0%), and T215FY (36.8%), while common NNRTI DRMs included K103NS (53.3%), Y181CIV (27.7%), and G190ASE (22.2%). In first-line ART failure, M184V significantly covaried with K70R, L74I, and M41L for NRTIs and K103N and G190A for NNRTIs. In second-line failure, the covariation with M184V extended to T215Y, M41L, and D67N for NRTIs and G190A, K103N, and K103S for NNRTIs. No significant covariation with M184V was observed in third-line treatment failures. Based on these covariations and on the effect of these mutations on available anti-HIV drugs, TDF (partial efficacy) and Doravirine (fully active) were identified as potentially suitable candidates in combination with ISL among patients failing the first, second, and third lines, and could serve as a valuable therapeutic option in LMICs facing similar treatment challenges.